SELECTIVE INFORMATION-PROCESSING IN BULIMIA-NERVOSA - Fairburn, C; Cooper, P; Cooper, M; Mckenna, F; Anastasiades, P (1991)
The Stroop color-naming paradigm was used to investigate information processing in bulimia nervosa. Patients with bulimia nervosa were compared with age-matched female controls as well as with a sample of men. It was found that the patients were slower than female controls were in color-naming words related to eating, shape, and weight, whereas there were no differences between the male and female controls. The findings suggest that bulimia nervosa is associated with the selective processing of information related to eating, shape, and weight and that this phenomenon may be restricted to those with an eating disorder of clinical severity.